2020
DOI: 10.1039/d0cp02713h
|View full text |Cite
|
Sign up to set email alerts
|

SerraNA: a program to determine nucleic acids elasticity from simulation data

Abstract: The resistance of DNA to stretch, twist and bend is broadly well estimated by experiments and is important for gene regulation and chromosome packing. However, their sequence-dependence and how bulk...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
40
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 89 publications
14
40
3
Order By: Relevance
“…With increasing improvements in population-scale human variation data, such as the Genome Aggregation Database (38), and predictive modeling to derive the structure of arbitrary DNA sequences (18)(19)(20)(21)(22)39), our study opens up new possibilities to mechanistically understand mutation rate variations in the human genome. In future studies, we may be able to use broader (9-mer) local contexts for predicting mutation rates, which we failed to do in our current study due to limitations from the 1000 Genomes dataset.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing improvements in population-scale human variation data, such as the Genome Aggregation Database (38), and predictive modeling to derive the structure of arbitrary DNA sequences (18)(19)(20)(21)(22)39), our study opens up new possibilities to mechanistically understand mutation rate variations in the human genome. In future studies, we may be able to use broader (9-mer) local contexts for predicting mutation rates, which we failed to do in our current study due to limitations from the 1000 Genomes dataset.…”
Section: Discussionmentioning
confidence: 99%
“…This technique probes the torsional elasticity by tracing the twist fluctuations of the ends of stretched DNA molecules of several kilobases length. The recent atomistic simulation study by Velasco-Berreleza et al [8] found a similarly strong length-dependence of the torsional fluctuations, although their asymptotic estimate indicates l T /2 ≈ 90 nm. We note here that l T at all length scales is not only determined by the twist stiffness C q , but also by other stiffnesses.…”
Section: B All-atommentioning
confidence: 93%
“…6. This strong length scale dependence of the torsional elasticity can potentially explain the divergence between estimates obtained with different experimental methods [8]. Studies that employ local probing methods find systematically lower stiffnesses as compared to studies in which larger length scales are considered, as is the case for magnetic tweezers (for a list of different estimates and methods used see supplemental of Ref.…”
Section: B Length Dependence Of Persistence Lengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism, thereby, constructs a mechanical “switch”, since the ultimate structural configuration can switch between different states in a mechanically dependent manner. The formation of such a sharp bend in one of these observed states is impossible to achieve in naked DNA, even for the most curved sequences (62, 63) unless base stacking and complementary hydrogen-bond pairing are disrupted on the double helix generating kinks or melting bubbles (36).…”
Section: Discussionmentioning
confidence: 99%